Mumukshūcẽ sĩhāvalokana mhaṇajeca mumukshūntīla nivaḍaka nibandha - Pāṅgārakara, Lakshmaṇa Rāmacandra (SAMP early 20th-century Indian books project ;, 1923)
Collection of articles on different subjects, first published in the Marathi monthly "Mumukshu" edited by the author.